NEWS Analysis Towards Youth Financial Competency Management - Isa, Khairunesa; Rahman Ahmad, Abd.; Md. Yusoff, Rosman; Ani, Fauziah; Isa, Fadzlunesa (International Journal of Engineering and Technology, 2018)
This is a descriptive study of the financial management competency of rural youth. Around 200 youths from areas of Parit Raja, Batu Pahat Johor participated as respondents for this study. Lack of knowledge in managing finances and imbalance in mitigating lifestyles are chief factors which caused youth to be within the highest group declared bancrupt in 2014.Â 36 items in the survey was ued as intrument for this study which are respondentsâ€™ background, spending pattern based on NEWS Analysis, competeny level in financial management and challenges faced in managing finances. Results yielded showed that expenditure pattern for youth in â€˜needsâ€™ are significantly higher than those in â€˜wantsâ€™. Eventhough the ratio is rather small which is 1:30, the level of competency of youth finance is rather high at the value of min 4.04. Nevertheless, the challenges faced by respondents are at an average level (min=3.14). In conclusion, rural youths has high level of literacy. This is due to the exposure obtained when they were young and spending pattern based on NEWS Analysis. Hence, even though youth faced obstacles they are nevertheless aware and know the steps which need to be taken to ensure the stability of their finances.Â